A STUDY ON MENTAL HEALTH OF HIGH SCHOOL STUDENTS - Raj Aman and Dr. Annapurna Gupta (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
In the life of a person, mental wellness is crucial. It has an impact on society as a whole as well as on the lives of specific people. No aspect of a person's life is outside the purview of psychological wellbeing. The phrase "mental health" does not refer to any one feature of the mind or one particular facet of the human character. A severe modernisation is taking place in the twenty-first century. The setting of a school is ideal for delivering mental health care. The media exposes kids to a wide variety of cultures, and sometimes so-called social media exposes them to the negative aspects of maladjustment, loneliness, addiction, and loss of social and emotional support. Children with stronger mental health do better academically and socially, according to studies.